Search for alternative control strategies of Drosophila suzukii (Diptera: Drosophilidae): laboratory assays using volatile natural plant compounds - Eben, Astrid; Sporer, Frank; Vogt, Heidrun; Link, Pille; Wink, Michael (Insects, 2020)
Drosophila suzukii (Diptera: Drosophilidae), is native to southeastern Asia and invaded Europe during the past decade. It causes serious economic damage in cherries and soft fruits. Control strategies rely on few insecticides with varying success. Due to environmental concern, the use of synthetic chemicals is restricted. Therefore, research effort is put into the quest for alternative substances applicable in chemical pest control. In laboratory assays, we tested 17 volatile plant compounds from different chemical classes for their contact toxicity, feeding modification, and oviposition repellency. Toxicity through contact with treated surfaces was evaluated after 1 h, 4 h, and 24 h; effects on food uptake were observed with capillary feeding (CAFE)—tests and oviposition trials compared egg numbers laid in raspberry medium with or without treated filter paper. Cinnamon oil and its components had the highest contact toxicity with an LC90 = 2–3%, whereas lemongrass oil, its main components, and farnesol were less toxic (LC90 = 7–9%), and geraniol was the least toxic. In CAFE tests, feeding stimulation was observed through 0.1% and 1% solutions of citronellol, lemongrass oil and farnesol. Cinnamon oil, cinnamaldhyde, and ethyl cinnamate were not consumed at a concentration of 1%. In the presence of citral, eugenol, and lemongrass oil, oviposition was reduced, and in the presence of limonene, no eggs were deposited. The natural products found most efficient in either bioassay will be further tested under field conditions.
Gesehen am 15.01.2021